2022
DOI: 10.1039/d2cp02252d
|View full text |Cite
|
Sign up to set email alerts
|

The kinetic energy of PAH dication and trication dissociation determined by recoil-frame covariance map imaging

Abstract: We investigated the dissociation of dications and trications of three polycyclic aromatic hydrocarbons (PAHs), fluorene, phenanthrene, and pyrene. PAHs are a family of molecules ubiquitous in space and involved in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…The maximum in Fig. 3 is at a slightly higher energy of 2.8 eV, possibly related to the higher electron impact energy of 70 eV as compared to the 40.9 eV photon energy used by Lee et al 25 We note that we have had to use the extended probability distribution in Fig. 3(a) to obtain a good agreement between Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The maximum in Fig. 3 is at a slightly higher energy of 2.8 eV, possibly related to the higher electron impact energy of 70 eV as compared to the 40.9 eV photon energy used by Lee et al 25 We note that we have had to use the extended probability distribution in Fig. 3(a) to obtain a good agreement between Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Theoretical calculations have also been reported in a number of experimental papers. 25,29–31,35–37,46–48,50…”
Section: Introductionmentioning
confidence: 99%
“…The astrochemistry community uses FLASH, to study how harsh, short wavelength radiation environment influences the chemical composition and abundance of molecules in space. Probing potential molecular reactions after irradiation with short wavelength pulses from FLASH thus generates insight into processes into the origins of molecules in the interstellar space [33,34].…”
Section: Present Status and Scientific Highlightsmentioning
confidence: 99%
“…Experimentally, the fragmentation of PAHs resulting from UV irradiation or collision has been investigated evidencing the dominant H, H 2 and C 2 H 2 loss channels and characterizing the stability of excited PAHs. [58][59][60][61][62][63][64][65][66][67][68][69][70] Collision-or photon-induced fragmentation has also been characterized in PAH clusters. 71 These experiments have demonstrated that the resulting mass spectra and identified dissociation channels can be interpreted schematically as belonging to one of two typical scenarios (see reviews 11,72 ), namely statistical or non-statistical fragmentation patterns which are determined by the nature of the excitation and the characteristic timescales of energy redistribution.…”
Section: Introductionmentioning
confidence: 99%